AI Nationalism in Shaping Global Governance - Riedho, M. Roehman Zainur (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2025)
The rise of AI nationalism is fundamentally reshaping global governance, creating a new geopolitical landscape defined by technological competition. This research investigates how nations are increasingly leveraging artificial intelligence not just as a tool, but as a cornerstone of national power, economic strategy, and identity. Through a qualitative analysis employing a constructivist lens, this study examines the historical narratives, theoretical underpinnings, and policy manifestations of AI nationalism. It utilizes purposive sampling to select case studies of the United States, China, Russia, India, and Indonesia, representing a spectrum of global actors from superpowers to key emerging economies. The findings reveal that AI nationalism is not monolithic, leading to a proposed typology of three distinct models: Geopolitical Supremacy, State-Led Developmentalism, and Pragmatic Sovereignty. The study demonstrates how historical legacies of technological rivalry and colonialism continue to shape contemporary policies, fostering a zero-sum competitive environment that fragments international regulatory frameworks and deepens power asymmetries. It concludes that the current trajectory of AI nationalism, while driving innovation, poses significant risks to global stability and equitable development. This research affirms the urgent need for hybrid, multistakeholder governance models that can reconcile national interests with the necessity for international cooperation, ensuring that AI's transformative potential serves collective global interests rather than entrenching existing hierarchies.